Resistance to causal agents of late blight and golden potato nematode of the modern cultivars of seed potatoes and their phytosanitary status in various agroclimatic zones of the European part of Russia - A. V. Khiutti; D. A. Rybakov; T. A. Gavrilenko; O. S. Afanasenko (Вавиловский журнал генетики и селекции)
The active expansion of foreign potato cultivars on the territory of the Russian Federation has led to a change in the dominant pathogen species and to the emergence of new pathotypes of causal agents of harmful potato diseases. The aim of the study was to evaluate resistance to Phytophthora infestans and Globodera rostochiensis of modern potato cultivars and determine the distribution of fungal and oomycetic diseases on potato cultivars in various agroclimatic zones of Russia. The resistance of 41 foreign cultivars was evaluated to pathotype Ro1 G. rostochiensis and to isolate VZR17 P. infestans with virulence genes 1.2.3.4.5.6.7.8.9.10.11. Resistant to G. rostochiensis were 38 cultivars. 57R marker of the H1 gene conferring resistance to the Ro1 pathotype of G. rostochiensis was detected in 96.6 % of the nematode resistant cultivars studied; susceptible varieties did not possess this marker. Absolute resistance to the causative agent of late blight was demonstrated by the cultivars Alouette and Sarpo Mira (score 9); high levels of resistance (score 6 and 7) were determined for the cultivars Evolution, Red Fantasy and Ricarda. The cultivars Baltic Rose, Damaris, Desiree, Gala, Labella, Laperla, Mia, Sanibel, Zekura, Queen Anne, Red Lady and ‘7 for 7’ were classified as susceptible, although the characteristics of originators indicated average resistance to late blight. A phytopathological test was conducted on 92 samples of 39 varieties of seed potatoes from four federal districts of the Russian Federation: Volga, NorthWest, Central and North Caucasus. Rhizoctonia solani, Fusarium spp. and Helminthosporium solani are most common on all varieties. 100 % defeat of tubers by H. solani was recorded in various regions on the cultivars Red Scarlett, Evolution, Labella, Colombo, Gala and Nevsky. Widespread Colletotrichum coccodes on tubers of the elite and 2nd reproductions of the potato cultivar Red Scarlett (50.0–71.4 %) was recorded in the Central District.